UPAYA PENGURUS KOPERASI MITRA ABADI GROUP DALAM MENINGKATKAN PENDAPATAN ANGGOTANYA DI KOTA BENGKULU - Friska Septiana; Bayu Pradikto; Ilham Abdullah (UNIB Press, Universitas Bengkulu, 2020)
Based on the results of the study and discussion, the conclusions are drawn : first, cooperative “Mitra Abadi Group” to increase quality of the members with the training. Second, the effort to increase incomes of members instill soul self-employed and devide the result of this, 50% to members 50% is gave ti cooperative. Third, the manager also face the problem is less capital, meanwhile supporting factors is charateristics of the settelment profitable. The writer hope is this research can become reference ti cooperative manager “Mitra Abadi Group” so that can serve again people. Key words : Increasing incomes, Cooperative